Operator models for delivering municipal solid waste management services in developing countries. Part A: The evidence base - Wilson,DC; Kanjogera,JB; Soos,R; Briciu,C; Smith,SR; Whiteman,AD; Spies,S; Oelz,B (Waste Management and Research, 2017)
This article presents the evidence base for ‘operator models’ – that is, how to deliver a sustainable service through the interaction of the ‘client’, ‘revenue collector’ and ‘operator’ functions – for municipal solid waste management in emerging and developing countries. The companion article addresses a selection of locally appropriate operator models. The evidence shows that no ‘standard’ operator model is effective in all developing countries and circumstances. Each city uses a mix of different operator models; 134 cases showed on average 2.5 models per city, each applying to different elements of municipal solid waste management – that is, street sweeping, primary collection, secondary collection, transfer, recycling, resource recovery and disposal or a combination. Operator models were analysed in detail for 28 case studies; the article summarises evidence across all elements and in more detail for waste collection. Operators fall into three main groups: The public sector, formal private sector, and micro-service providers including micro-, community-based and informal enterprises. Micro-service providers emerge as a common group; they are effective in expanding primary collection service coverage into poor- or peri-urban neighbourhoods and in delivering recycling. Both public and private sector operators can deliver effective services in the appropriate situation; what matters more is a strong client organisation responsible for municipal solid waste management within the municipality, with stable political and financial backing and capacity to manage service delivery. Revenue collection is also integral to operator models: Generally the municipality pays the operator from direct charges and/or indirect taxes, rather than the operator collecting fees directly from the service user.